Sonate für das Piano-Forte von L. van Beethoven. Op. [2 No. 2]. Neue correcte Ausgabe. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; Frankfurt am Main; Jos. Ant. Löhr, 2022)
Edition of Beethoven's Piano Sonata no. 2 in A major, op. 2, no. 2, published ca. 1830-1835 by Jos. Ant. Löhr in Frankfurt am Main as part of a series of "neue correcte Ausgabe(n)" (new correct editions).